2017
DOI: 10.1093/intqhc/mzx004
|View full text |Cite
|
Sign up to set email alerts
|

Professional attitudes toward incident reporting: can we measure and compare improvements in patient safety culture?

Abstract: Because the doctors' reporting rates increased during the study period, doctors may be more likely to report adverse events than nurses, although nurses reported more events. Incident reporting trends and other routinely collected risk indicators may be useful to improve our understanding and measurement of patient safety issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…Consistent with our results, previous studies have found that nurses reported more incidents than other professions. [18][19][20][21] Some researchers have argued that doctors, in particular, are often skeptical and have not fully accepted the incident reporting system as an opportunity for improving quality of care. 19 Our results from the work units where incidents were reported were also consistent with other studies that reported that incident reports were primarily made within a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, previous studies have found that nurses reported more incidents than other professions. [18][19][20][21] Some researchers have argued that doctors, in particular, are often skeptical and have not fully accepted the incident reporting system as an opportunity for improving quality of care. 19 Our results from the work units where incidents were reported were also consistent with other studies that reported that incident reports were primarily made within a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Some researchers have argued that doctors, in particular, are often skeptical and have not fully accepted the incident reporting system as an opportunity for improving quality of care. 19 Our results from the work units where incidents were reported were also consistent with other studies that reported that incident reports were primarily made within a clinical setting. 22 Furthermore, consistent with our finding about training, participation in monthly quality or safety conferences in US hospitals has increased the reporting rate of trainees from 27.6% to 46.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Reporting practice errors or near misses are fundamental to quality improvement and patient safety [23]. Notifications of practice errors are important for: recording and communication of issues to management; assessment of risks and harm; rectification; and interventions and practical strategies to improve patient safety [20,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Eighth, the data collection of this study was conducted in 2010. Considering both evolving and persistent trends in the safety culture of acute health care institutions in high‐income countries over the recent decades, the relevance of these findings need to be updated. Ninth, an analysis of convergent validity (Appendix S2) showed that the outcome, perception of safety in the OR, was weakly correlated with other items or scales related to safety.…”
Section: Discussionmentioning
confidence: 99%